Determining directions for improving technology transfer in the European Union within the framework of the EUROPEAN INNOVATION ACT - Ostapenko, Iuliia; Holieva, Nadiia; Borysov, Igor; Sivash, Olena; Lisohorova, Kateryna (Eastern-European Journal of Enterprise Technologies, 2026)
A system of regulatory tools and procedures that regulate technology transfer in the European Union (EU) has been considered in this study in view of the adoption of the EUROPEAN INNOVATION ACT ("EIA"). Techniques that define technology and its transfer in the EU were investigated, as well as the directions for their improvement in view of EIA adoption. During the study, it was established that the process of regulating technology transfer in the EU is not uniform. It has been proven that the current model of regulatory influence in the EU is not focused on simplifying and stimulating technology transfer. Its main task is to ensure the possibility of achieving socially useful tasks of a public nature. The need for improving the process of regulating technology transfer within the European Union has been substantiated. Directions for improving the regulation of technology transfer in the EU have been defined, namely: a) systematization of regulatory influence on technology transfer around technology; b) formation of a separate independent definition of technology; c) consolidation of the concept of forms of technology; d) formation of means of ensuring the private interests of technology transfer participants. It was determined that the main place (form) of change in the regulation of technology transfer in the EU should be the Horizon Europe Framework Program and the EUROPEAN INNOVATION ACT. The study is aimed at formulating proposals for improving the regulatory processes of technology transfer in the EU. The main achievement is that the results of this work could be used to improve the official rules of technology transfer in the EU. They could also be applied to form strategic public management decisions, state policy on the circulation of innovations; they might serve as the basis for further scientific research on these issues